2010
DOI: 10.1097/spc.0b013e32833d303b
|View full text |Cite
|
Sign up to set email alerts
|

Updates on osteonecrosis of the jaw

Abstract: Purpose of review-Osteonecrosis of the Jaw (ONJ) in an uncommon condition noted to occur in patients with cancer receiving intravenous bisphosphonates. The etiology of ONJ remains unknown. The leading hypotheses addressing the mechanism of ONJ are reviewed here.Recent findings-The present clinical data suggests that ONJ may occur in approximately 5% of patients with metastatic bone disease. The ability to predict an individual's risk of developing ONJ remains elusive. It is likely that an altered bone microenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
1
19
0
5
Order By: Relevance
“…Results from animal studies suggest that vitamin D may play a predominant role in mandibular anabolic bone formation (Liu et al, 2009), and may exert positive effects on fracture healing (Fu et al, 2009). Vitamin D deficiency has also been associated with compromised osseous healing in the oral cavity in bisphosphonate-associated osteonecrosis of the jaw pre-clinical studies, supporting a role for vitamin D in bone healing in the oral cavity (Hokugo et al, 2010;Yamashita et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Results from animal studies suggest that vitamin D may play a predominant role in mandibular anabolic bone formation (Liu et al, 2009), and may exert positive effects on fracture healing (Fu et al, 2009). Vitamin D deficiency has also been associated with compromised osseous healing in the oral cavity in bisphosphonate-associated osteonecrosis of the jaw pre-clinical studies, supporting a role for vitamin D in bone healing in the oral cavity (Hokugo et al, 2010;Yamashita et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that the bone-remodeling rate is high in the jaw [14]. Thus, BPs may have a greater impact on the health of the jawbones than on other bones.…”
Section: Introductionmentioning
confidence: 96%
“…Although the etiology of BRONJ remains unclear, potential mechanisms have been proposed, including the over-suppression of bone turnover, suppression of angiogenesis, infection, soft tissue toxicity, and immune dysfunction [4,8,14]. It has been suggested that the bone-remodeling rate is high in the jaw [14].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of bisphosphonate-related osteonecrosis of the jaw has been speculated to be due to the impact of bisphosphonates on osteoclast survival, epithelial cells, endothelial cells, and immune cells (Yamashita et al , 2010). Bisphosphonates exert their anti-resorptive activity by suppression of osteoclasts.…”
Section: Dental Implant and Implant-related Bone Augmentation Proceduresmentioning
confidence: 99%